Persepsi Penumpang Mengenai Sweeping Baggage pada Maskapai Citilink terhadap Kepuasan Penumpang di Bandar Udara Ahmad Yani Semarang - Rafi Luqmanul Hakim; Desiana Rachmawati (Ebisnis Manajemen, 2025)
During Sweeping, of course the Sweeping process can cause various perceptions, whether positive or negative. The purpose of this study is to determine whether there is an influence between passenger perceptions regarding sweeping baggage on passenger satisfaction and to determine how much influence there is between passenger perceptions regarding sweeping baggage on passenger satisfaction of Citilink Airlines at Ahmad Yani Airport, Semarang. This research uses a quantitative methodology, employing research instruments for data collection and statistical analysis to evaluate the specified hypotheses. This research uses a survey methodology involving 100 participants. The data analysis procedures used include instrument testing, simple linear regression, t-test, and determination test (Adjusted R Square). The results of this study show the t-value of the passenger perception variable of (0.000). Which means that passenger perceptions regarding sweeping baggage have a significant influence on Citilink Airlines passenger satisfaction at Ahmad Yani Airport, Semarang. The results of the questionnaire found that the passenger perception value regarding sweeping baggage was good with a percentage value of 85.6% and the results of the passenger satisfaction value were 82.7%. And the Adjusted R Square value is 0.693, which means that passenger perception has an influence of 69.3% on passenger satisfaction.